Framing Agricultural Labor Issues: An Analysis of News Coverage of the H-2A Program - Erica D Summerfield; Cara Lawson; Finn Garrison; Lauren Chase (Journal of Applied Communications, 2024)
The H-2A program is a temporary agricultural worker program created by the Immigration Control and Reform Act in 1987 that allows agricultural employers in the United States to hire nonimmigrant foreign workers when a shortage of domestic workers exists. The H-2A program reduces labor shortages and helps to offset the incline in undocumented immigrants in the U.S., but the program is complex and continues to evolve as labor needs in agriculture continue to increase. Issues in agriculture, like the H-2A program, can be difficult to understand and often require specialized communication efforts. Researchers have found the news media help to shape public perceptions of complex issues, and news framing is often used by journalists to simplify details and make sense of unfolding information. This study analyzed the frequency of media coverage, frames, and sources used to communicate information about the H-2A program in newspapers located in the four states with the most certified H-2A workers – Florida, California, Georgia, and Washington. Newspaper articles pertaining to the H-2A program communicated information largely through a “policy/government” frame. The most frequently referenced sources throughout these articles were nongovernmental organizations (NGOs) or NGO representatives, followed closely by elected officials. Recommendations for future studies involving media framing and the H-2A program are discussed.
Keywords: Framing; Issue Communication; H-2A; Media Sources